2018
DOI: 10.1007/s11248-018-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to coronavirus infection in amino peptidase N-deficient pigs

Abstract: The alphacoronaviruses, transmissible gastroenteritis virus (TGEV) and Porcine epidemic diarrhea virus (PEDV) are sources of high morbidity and mortality in neonatal pigs, a consequence of dehydration caused by the infection and necrosis of enterocytes. The biological relevance of amino peptidase N (ANPEP) as a putative receptor for TGEV and PEDV in pigs was evaluated by using CRISPR/Cas9 to edit exon 2 of ANPEP resulting in a premature stop codon. Knockout pigs possessing the null ANPEP phenotype and age matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 45 publications
(59 reference statements)
0
82
1
Order By: Relevance
“…Researchers from the Roslin Institute have proposed to edit the domestic pig inducing this variation in RELA with the aim to confer disease resilience to this virus [55,56]. In another study, CRISPR has also been used to produce Coronavirus resistant pigs, by editing a putative receptor of the transmissible gastroenteritis virus [57]. In China, edited cows with increased resistance to tuberculosis were produced through CRISPR [10].…”
Section: Stage Of Embryosmentioning
confidence: 99%
“…Researchers from the Roslin Institute have proposed to edit the domestic pig inducing this variation in RELA with the aim to confer disease resilience to this virus [55,56]. In another study, CRISPR has also been used to produce Coronavirus resistant pigs, by editing a putative receptor of the transmissible gastroenteritis virus [57]. In China, edited cows with increased resistance to tuberculosis were produced through CRISPR [10].…”
Section: Stage Of Embryosmentioning
confidence: 99%
“…Previous work from our lab showed that ANPEP KO pigs are completely resistant to infection with TGEV (Whitworth et al, 2018). We tested the ability of PDCoV to infect ANPEP KO pigs.…”
Section: Pdcov Infection Of Anpep Wt and Ko Pigsmentioning
confidence: 99%
“…The use of genome editing to generate pigs lacking aminopeptidase N successfully showed that pigs resistant to TGEV infection could be generated. However, the edited animals remained susceptible to PEDV infection (Whitworth et al, 2019). Aminopeptidase N is important for peptide digestion in the small intestine and knockout mice were shown to have delayed mammary gland development.…”
Section: Pigsmentioning
confidence: 99%